Natural Categorization: Electrophysiological Responses to Viewing Natural Versus Built Environments - Mahamane, Salif; Wan, Nick; Porter, Alexis; Hancock, Allison S.; Campbell, Justin; Lyon, Thomas E.; Jordan, Kerry E. (Frontiers in Psychology, 2020)
Environments are unique in terms of structural composition and evoked human experience. Previous studies suggest that natural compared to built environments may increase positive emotions. Humans in natural environments also demonstrate greater performance on attention-based tasks. Few studies have investigated the mechanisms underlying these phenomena or probed these differences from a neural perspective. Using a temporally sensitive electrophysiological approach, we employ an event-related, implicit passive viewing task to demonstrate that, in human prefrontal cortex, built environments elicit a greater late positive potential (LPP) than natural environments, resulting in a faster return of activation to pre-stimulus baseline levels when viewing natural environments. Previous LPP research suggests faster LPP recovery time is related to pleasant experiences, whereas slower LPP recovery is related to less positive experiences. Our research thus provides neural evidence suggesting natural environments are perceived and experienced differently from built environments, converging with previous behavioral findings and theoretical assumptions from environmental psychology.